Workplace factors and work-life balance among employees in selected services sectors - Wong, Pui Yee; Nur Fatihah, Abdullah Bandar; Jamayah, Saili (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study is conducted to examine the relationship between workplace factors and work-life balance among employees in selected services sector. The independent variables of this study comprise of supervisor support, co-worker support and flexible working arrangement; whereas the dependent variable in this study is work-life balance. The quantitative research method is selected and questionnaire is used as the research instrument to collect data. There are 98 samples randomly selected from selected services sector (N=110). The data collected is analysed by using Statistical Packages for Social Science Version 22.0 (SPSS Version 22.0) software. The Spearman rho test is used to test the relationship between independent and dependent variables. The results revealed that there are positive relationship between work-life balance with supervisor support, co-worker support and flexible working arrangement. In short, the workplaces factors contribute to work-life balance under Malaysia context. This study gives an insight to the organization in designing an appropriate system to enhance work-life balance.